On how adopting an ELF pedagogical perspective can help CLIL teachers. - Pineda-Hernández, Inmaculada Concepción (Dr. Kovac Verlag, 2022)
English as a global language has visibly undergone a number of changes and its fluidity and variability both functional and formal are evident (e.g. Archibald et al. 2011; Baird et al. 2014; Seidlhofer 2011). Current research on English as a Lingua Franca (ELF) and ELF Pedagogy suggests that English Language Teaching (ELT) and Content and Language Integrated Learning (CLIL) practitioners feel empowered when given the possibility to explore this fluidity and their teaching practice can be less constrained by traditional English as a native language (ENL) principles (Yalcin et al. 2020). The current paper will explore a number of key concepts in ELF research particularly focusing on the still developing ELF pedagogical perspective and it will then move on to the description of a blueprint to combine an ELF standpoint with CLIL. The paper concludes with a theoretical discussion on how this model could be implemented with specific examples of multimedia resources that can be created both by teachers and students.
Keywords: Segunda lengua - Adquisición; English as a lingua franca; CLIL; Teacher Education